PENGGUNAAN DANA DESA RAWANG OGUNG KECAMATAN KUANTAN HILIR SEBRANG KABUPATEN KUANTANSINGINGI TAHUN 2017 - Sijor Deri; Rury Febrina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was conducted in Rawang Ogung Village, Kuantan Hilir Sebrang District, Kuantan Singingi Regency. This study aims to determine the use of Village Funds in Rawang Ogung Village, Kuantan Hilir Sebrang Subdistrict, Kuantan Singingi Regency in 2017. In Law Number 6 of 2014 Concerning Villages it is explained that the Village is a legal community unit that has territorial boundaries that are authorized to regulate and take care of Government affairs, the interests of the local community based on community initiatives, original rights, and / or traditional rights that are recognized and respected in the Government system of the Unitary State of the Republic of Indonesia. In the Regulation of the Minister of Village (permendes) for the development of underdeveloped regions and transmigration Number 5 of 2016 and the Regulation of the Minister of Village (permendes) for the development of underdeveloped areas and transmigration Number 22 of 2017 concerning Priorities for the Use of Village Funds in 2016 and 2017, the principle of the Use of Village Funds states that: Article 2 : Village Funds sourced from the APBN are used to fund the implementation of Village authority based on village origin rights and local scale authority that is regulated and managed by the Village. In article 3 that: Village funds are prioritized to finance development spending and empower the village community. In Article 4: The use of Village Funds is stated in the Village expenditure priorities agreed in the Village Conference. The research method used in this study is qualitative. Data collection techniques are interviews and documentation with data analysis done descriptively. This study examines the use of Village Funds by the Rawang Ogung Village government and how the village authorities realize the Village Fund in the use of Village Funds in Rawang Ogung Village in 2017. The results of this study indicate the use of Village Funds in Rawang Ogung Village in 2017 has not been implemented effectively and efficiently, as evidenced in the field of development implementation and the field of village government. The implementation of the village development was not carried out entirely in accordance with the planning carried out causing the roads that could not be used properly by the community, there were also other obstacles such as not understanding the duties and functions of the village government, lack of communication and lack of transparency to the community. Keywords: Use, Village Funds, Use of Village Funds.